2022
DOI: 10.3389/fendo.2022.966120
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes the growth and development of lambs by increasing growth hormone and testosterone, targeting on apoptosis signaling pathway and intestinal microflora

Abstract: Melatonin is an indole-like neuroendocrine hormone. A large number of studies have shown that melatonin can improve production performance of ewes, but it is not clear in lambs. In this study, the growth and development of the 2-month-old lambs implanted with melatonin were monitored for 60 days. The results showed that the growth rate of body weight and body skew length of lambs with melatonin treatment were significantly improved compared to the controls. The similar results were also observed in red blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…About the 6weeks groups, the GH levels were: group (A) ( Depending on the table above that shows mean±standard error, we noticed that Growth hormone and leptin increase with extension in duration of melatonin intake. Some studies show that melatonin effect the GH level in mice, the GH level increase with the intake of melatonin [24,31]. There is some evidence that chemically, melatonin can behave somewhat like a growth hormone-releasing peptide and trigger the hypothalamus to tell the pituitary gland to make and release more GH.…”
Section: Resultsmentioning
confidence: 99%
“…About the 6weeks groups, the GH levels were: group (A) ( Depending on the table above that shows mean±standard error, we noticed that Growth hormone and leptin increase with extension in duration of melatonin intake. Some studies show that melatonin effect the GH level in mice, the GH level increase with the intake of melatonin [24,31]. There is some evidence that chemically, melatonin can behave somewhat like a growth hormone-releasing peptide and trigger the hypothalamus to tell the pituitary gland to make and release more GH.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin has been used to improve reproductive activity in different animals. For example, in sheep, the subcutaneous embedding of melatonin promoted the growth and development of lambs [ 29 ]. As mentioned above, Peng et al, gave melatonin to early gestated sows and also tested their oxidative stress responsibility [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to increased provision of trophic signals (represented by increased Serum IGF-1 secretions) and/or blood-borne metabolites (glucose, cholesterol, and lipids) [ 7 ]. Another study reported that melatonin implantation improved the sheep growth and development via increasing the growth hormone release [ 24 ]. In the same context, appropriate thyroid gland function and activity of thyroid hormones (TH) are considered crucial to sustain productive performance in domestic animals (growth, milk, hair fiber production), and circulating TH can be considered as an indicator of the metabolic and nutritional status of the animals [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%